Cross-cultural differences in the preference for brand prominence of luxury products. - Chen, Crystal Wanjing. (2011)
This study investigates the cross-cultural difference of women in the preference for brand prominence of luxury products as well as the motivations behind these preferences. 14 motivational scales were included in the research, and culture was identified as the moderating factor of the study. As such, participants were either Eastern- or Western-primed.